The balancing act of combining school and football in the transition from a non-professional club into junior-elite academy football - Solhaug, M.; Høigaard, R.; Sæther, S. A. (Scandinavian Journal of Sport and Exercise Psychology, 2021)
Football players in the transition from junior-to-senior are usually involved in dual careers, combining school and football - a process that makes them dependent on a holistic talent-development journey. The aim of the current study was to describe how male junior elite football players (N=10; 5=living at home, 5=living away from home) perceived stressors in the transition from a non-professional club into a junior elite academy. Furthermore, the school transition (between lower- and upper-secondary school) and social transition (based on the school and football transitions) as a consequence of the football transition into academy football. Based on Wylleman and Lavallee`s (2004) and Stambulova`s (2003) models, the data were analysed based on the following three levels in the transitions: athletic, academic - and psycho-social. The main perceived stressors in the football transition (athletic level) were new performance demands, which impacted them both physically (e.g., quality of training) and psychologically (e.g., self-esteem and well-being). Perceived stressors in the school transition (academic level) were related to increased academic workload and expectations, and academic achievement. Perceived stressors related to the social transition (psycho-social level) among the players that have chosen to live away from home were new roommates and doing more housework, even though they adapted quickly to the new requirements. Both groups highlighted the importance of having a social network (friends, leisure activity) outside of football, so they got to relax and not always think about football or school. The study findings suggest that maintaining dual careers introduces stressors for most players - independent of living at home or away from home.